The role of Bcl-2 protein, Bax protein and there ratio in peripheral blood lymphocytes of asthmatic patients - Jaffar, Israa F.; Ali, Musaab H; Kadhim, Haider S. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Asthma is an inflammatory airway disease; this inflammatory response can be attributed to reduced lymphocyte apoptosis in peripheral blood and in airway tissues. The mechanism behind this could be attributed to decreased Bcl2 protein and increase Bax protein in peripheral blood lymphocytes of asthmatic patients. Aim: to explore the mechanism behind decreased lymphocyte apoptosis in peripheral blood of asthmatic patients at cellular level. Method: Ninety four subjects; (44) control and (50) patients were included in this study during the period from (2003) to (2004). The aspirated lymphocytes for each individual were prepared and stained by immunocytochemistry to study the percentage of antiapoptotic Bcl-2 protein, pro-apoptotic Bax protein and their ratio. Results: Our results showed that the percentage of Bcl2 protein in peripheral blood lymphocyte of asthmatic patients were significantly higher than control (33.23±11.56, 21.47±4.16)(P=<0.00001). The percentage of Bax protein in peripheral blood lymphocyte in asthmatic patients was significantly lower than the control (21.43±6.88, 24.89±4.8) (P-O.0323). Bcl2/Bax ratio was positive in asthmatic patients there was significant difference in comparison with the control (1.68±0.57, 0.87 ± 0.17) (P=<0.00001). Conclusion: This study clarifies the role of these 2 proteins in the process of reduction of apoptosis in peripheral blood lymphocytes of asthmatic patients.